Association of non-phthalate plasticizer exposure during early pregnancy with gestational diabetes mellitus: The potential mediation effect of plasma lipidome - Yingying Mao; Shuqin Tang; Huan Liu; Qing Huang; Da Chen; Yuanyuan Li; Fengjiang Sun; Wei Huang (Ecotoxicology and Environmental Safety)
Given the well-documented endocrine-disrupting effects of phthalate plasticizers (PAEs) on human health, their use has been subjected to stringent regulatory restrictions, prompting a global shift toward non-phthalate plasticizers (non-PAEs) as alternatives. While epidemiological evidence has established significant associations between PAE exposure and gestational diabetes mellitus (GDM), the potential role of non-PAEs in GDM pathogenesis represents a critical knowledge gap in environmental epidemiology. To address this, we conducted a case-control study nested within a well-established prospective birth cohort in Wuhan, China, comprising 286 GDM cases and 286 matched healthy controls. Plasma concentrations of 10 non-PAEs were quantified with high detection frequencies (≥ 70 % for six species). Using multivariable conditional logistic regression and restricted cubic spline regression models adjusted for maternal age, pre-pregnancy body mass index, and other covariates, we identified significant positive associations between gestational exposure to dimethyl azelate (DMAZ), trihexyl trimellitate, di(2-ethylhexyl) maleate, and dibutyl fumarate and elevated GDM risk. In addition, the Bayesian kernel machine regression (BKMR) model further revealed a joint effect of the non-PAE mixture exposure on GDM risk, and DMAZ and diisobutyl adipate/dibutyl adipate (DiBA/DnBA) were identified as key contributors to the joint effect. Our results also demonstrated significant mediation effects of selected lipid molecules (especially phosphatidylcholine and lysophosphatidylcholine) on the associations of DMAZ and DiBA/DnBA with GDM risk. These findings contribute to a deeper understanding of the environmental stressors associated with the development of GDM, as well as the underlying biological mechanisms involving lipid metabolism.